A new meshing criterion for the equivalent thermal analysis of GaAs PHEMT MMICs. (January 2017) - Xu, Xiuqin; Mo, Jiongjiong; Chen, Wei; Wang, Zhiyu; Shang, Yongheng; Wang, Yang; Zheng, Qin; Wang, Liping; Huang, Zhengliang; Yu, Faxin
Abstract: In this paper, a new meshing criterion for the equivalent thermal analysis of GaAs PHEMT MMICs (Monolithic microwave integrated circuit) is proposed. Based on the meshing criterion, an equivalent thermal model of GaAs PHEMTs with remarkably reduced mesh complexity is established, and the simplification of both layout pattern and vias of MMICs are performed. Theoretical analysis is applied for the calibration of the equivalent thermal model. Assisted by the meshing criterion, chip-level simulators are capable to obtain the peak temperature of MMICs without using averaging approximations, and achieve considerably high simulation accuracy. As examples, two MMIC power amplifiers are designed and implemented using GaAs PHEMT process. Thermal simulation and measurement results obtained with ANSYS ICEPAK and infrared thermography, respectively, show high consistency. The proposed meshing criterion can be applied to improve the accuracy of thermal analysis of MMICs, and the obtained precise peak temperature can be used to effectively assess the power threshold of the designed amplifiers in reliability tests.